Ethnobotanical study of plants used by the lacustrine population of southern Benin in the treatment of malaria - AGBANGNAN DOSSA, COKOU PASCAL (My University, 2016)
This study aims to identify the plants used by the South Benin lacustrine population in the treatment of malaria. From august to October 2014, the population of “Ganvie” and “Aguegues-Daho” were interviewed by means of survey forms during a series of interviews. It appears from this study that the southern Benin lacustrine population hasn’t antimalarial plants in their immediate environment and purchases them on two markets, Ouando (Aguegues-Daho) in Porto-Novo and Calavi Topka (Ganvie) in Abomey-Calavi. The majority of population (Ganvie: 51.85%; Aguegues-Daho: 65.38%) associates the plants to drugs in the treatment of malaria to palliate inefficiency and inaccessibility of antimalarial drugs. In total 47 species of medicinal plants have been identified, distributed in 44 genera and 27 botanical families. The most represented are the Rubiaceae (6 genera and 7 species), the Papilinoideae, the Sterculiaceae and the Bignoniaceae (3 genera and 3 species). These plants enter in the formulation of 12 recipes in the treatment of malaria in children, pregnant women and adults. These recipes are prepared by decoction and administered orally.
Keywords: Ethnobotanical investigation; plant; malaria; recipe